ICT and artistic competence (Journal of Parents and Teachers, 2014)
The artistic competency includes the appreciation of creative expressions through every possible manifestation and this is why this competency is related to the other ones. When we surf the net we soon get surrounded by images and audiovisual messages, therefore IT’s are a necessary tool to develop the artistic competence.
Keywords: IT’s; basic competencies; artistic competency; new technologies